Ineffectiveness of Qanun Jinayat Against Child Violence: A Normative Study in Aceh, Indonesia - Muksana Pasaribu; Elwi Danil; Kurnia Warman; Irzal Rias (International Journal of Law and Society, 2026)
Violence against children remains a persistent and escalating problem in Indonesia, particularly in Aceh Province, where Qanun Jinayat formally enforces Islamic criminal law. Despite the existence of this regional legal framework alongside the national Child Protection Law (Law No. 35 of 2014), the rate of child violence in Aceh has continued to rise, suggesting a fundamental gap between legal norms and their implementation. This study aims to analyze the effectiveness of Qanun Jinayat in handling cases of violence against children in Aceh, with specific focus on the normative discrepancy between Qanun Jinayat and the Child Protection Law in terms of sanctioning systems and law enforcement outcomes. Employing a normative legal research method with legislative and case approaches, this study analyzes primary legal materials including Qanun Aceh No. 6 of 2014 on Jinayat Law, Law No. 35 of 2014 on Child Protection, and relevant court decisions. The findings reveal that Qanun Jinayat has not been effective in reducing child violence due to a dualism of legal provisions. While sanctions under the Child Protection Law are cumulative and more severe, those under Qanun Jinayat are alternative and comparatively lighter, resulting in suboptimal deterrence. This study is limited to normative legal analysis based on legal documents and court decisions, and does not encompass field-based empirical data. Theoretically, this study contributes to the discourse on legal pluralism and the hierarchy of norms in Indonesia's special autonomy regions. Practically, the findings offer policy  recommendations for harmonizing Qanun Jinayat with national child protection standards to strengthen law enforcement in Aceh. This study provides original value by being among the first to systematically examine the normative conflict between Qanun Jinayat and the Child Protection Law, specifically in the context of child violence cases.